THE GUARDIAN COUNCIL AS A PROCEDURAL INSTRUMENT: THE PRINCIPLES OF JUDICIAL SPEED AND ACCESS TO JUSTICE - Quintanilha da Silva , Pyerre (Revista Gênero e Interdisciplinaridade, 2022)
Accessing justice means having effective and socially just solutions for the parties to the litigious and this implies delivering the solution to the conflict in a reasonable time while ensuring legal certainty. The reasonable duration of the process is thus an indispensable factor for the maintenance of justice and in Brazil the problem in the delay of the deadlines of the judiciary has been a constant. Specifically with regard to the courts of childhood and youth, the National Council of Justice points out that one of the problems that occurs to complete the processes within this reasonable period in order to effect the principle of the best interest of the child is exactly the lack of multidisciplinary team specialized in the courts. This factor could be solved through the use of the previous diagnostic report made by the multidisciplinary teams of the guardianship council. This ‘removes its authority from the Statute of the Child and Adolescent, has structured teams that would work in order to overcome this stage that causes delay to the processes, with legal certainty and in the best interest of the minor.